Opportunities and costs of tourism for a new Humanism - Bizzarri Carmen (Miscellanea Geographica: Regional Studies on Development, 2016)
The first part of this paper describes the flow of tourism on a national and international scale, emphasizing the role that entertainment tourism and theme parks play globally. Following these preliminary remarks, the second part of the paper presents the positive and negative economic effects of leisure tourism opportunities at the European and regional level. The third part of the paper analyses the environmental aspects of tourism and entertainment tourism. It shows that sustainable tourism development can be an essential condition for the protection of natural and cultural resources. Finally, the fourth part summarizes some of the most important social issues arising from tourism activities, among them the conflict between residents and tourists on the exploitation of resources and the demonstration effect deriving from the consumption of resources. To avoid this spoliation and destruction of the destination (land and local community), the paper suggests a new Humanism based on Catholicism as a way to realize a sustainability utopia.